Corpo-criança aprisionado em tempo integral: indagações sobre o “currículo da conformidade” e o “currículo da expressividade” na escola - Brito, Lucas Xavier (Universidade Federal do Tocantins, 2018)
The research is related to "search line" Curriculum, Teacher Training and Knowledge Faculty, the Graduate Program in Education of the Federal University of Tocantins, based on the Group's studies Research and Extension Curricular Policies Education – NEPCE. Had the "object of study" the body of children in school full-time Fr. Josimo in Palmas – TO. The "overall objective" of the research is to understand how the activities of the ETI curriculum, whether the common core or diverse part, act on body culture movement of children. His "specific objectives" are guided by: 1) understand their ways around the historiographical debate on the school full-time: full training, full-time school and extended school day; 2) understand the concept of body and corporeality in contemporary times; 3) identify the curricular activities, both the compulsory subjects, as the complementary activities, as they (in) form and / or make up the body and corporeality of children in school full-time for the curriculum of the Early Years of Elementary School: 1) in the classroom of compulsory subjects (English Language, Mathematics, History, Geography, Science); 2) supplementary activities (swimming, dancing, volleyball, ballet, music); 3) in the Physical Education classes, 4) in the courtyard and free area. The "methodological foundations" of the research are based on a qualitative approach. The Master results from the literature search and document analysis with the arguments of the critical etnopesquisa and etnopesquisa-training, which are established as a description, a "re-presentation" of the interpretative and symbolic meanings, trying to describe to understand the understanding given to the body and corporeality in the curricular activities of the school full-time. The main theoretical references: Miguel Arroyo and Mauricio Roberto (2012), Alice and Elizabeth Lopes Macedo (2011), Tomaz T. Silva (1995, 1999), Florence Braunstein & Jean-François Pépin (1999), Rodrigo Carvalho (2006), Jocimar Daólio (2007), Olavo Feijó (1998), Michel Foucault (1984, 2008), Sergio Barbosa (1996), Giovanina Freitas (2004), Bell Hooks (1999), Guacira Louro (2000, 2001, 2010), Roberto Macedo (2006), Damião Rocha (2005, 2010, 2013, 2014th and 2014b), Carmen Smith (2007). The work is indicative that the full-time school has been billed as "educational territories", but has become a "non-place" body-child. Consequently the bodies are scrupulously watched and observed and / or energized and persuaded, which speak against the prospect of an "integrated curriculum", to dismantle nuclear activities of secondary activities in their curriculum design training. These curricular practices (in) form the children's curriculum moments based on rules, discipline and heteronomous moral, and others who may be autodisciplinares, thus creating two curriculum models: a "compliance curriculum" and another "curriculum expressiveness "applied alone, hierarchical and obligatory, even in complementary activities that should enrich and become articulator axis between the core curriculum activities and secondary curricular activities.